2022
DOI: 10.3390/nu14081579
|View full text |Cite
|
Sign up to set email alerts
|

Are People with Obesity Attracted to Multidisciplinary Telemedicine Approach for Weight Management?

Abstract: The forced isolation due to the COVID-19 pandemic interrupted the lifestyle intervention programs for people with obesity. This study aimed to assess: (1) the behaviors of subjects with obesity towards medical care during the pandemic and (2) their interest in following a remotely delivered multidisciplinary program for weight loss. An online self-made survey addressed to subjects with obesity was linked to the official website of our institute. Four hundred and six subjects completed the questionnaire (90% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Second, the limited number of electronic databases considered during the searching process may have contributed to limit the discussion of the results. Third, studies utilizing telemedicine approaches were not considered in the present study, although this modality seems to be a new frontier gaining even more attention into research and clinical setting in obesity management [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the limited number of electronic databases considered during the searching process may have contributed to limit the discussion of the results. Third, studies utilizing telemedicine approaches were not considered in the present study, although this modality seems to be a new frontier gaining even more attention into research and clinical setting in obesity management [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from a practical point of view, we could speculate that fitness coaches or therapists could benefit from designing their training programs using an external focus, not only with individuals with obesity in a gym-based setting, but also online in the context of telerehabilitation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for multi-strategy lifestyle interventions, the addition of knowledge about health and nutrition is necessary to avoid energy-compensatory behavior and achieve ideal weight loss. 43 Many studies have shown that health and/or nutrition education programs improve participants' health knowledge and behaviors, such as reduced consumption of sweets, soft drinks, high-fat products, and processed meats, increased lean meat and poultry intake, and increased amounts of physical activity, and modifications in eating habits and sedentary behavior further reduced body weight and cardiovascular risk. 44 These findings suggest that health education not only can increase health and nutrition knowledge about obesity but also can trigger beneficial behavioral changes, such as better eating patterns and more time for physical activity, which may further lead to weight loss.…”
Section: N Utriti On Life S T Yle Tre Atments For Ob E S E Patientmentioning
confidence: 99%
“…These adaptations are likely to lead to lower‐than‐expected weight loss or even weight relapse. Therefore, for multi‐strategy lifestyle interventions, the addition of knowledge about health and nutrition is necessary to avoid energy‐compensatory behavior and achieve ideal weight loss 43 . Many studies have shown that health and/or nutrition education programs improve participants' health knowledge and behaviors, such as reduced consumption of sweets, soft drinks, high‐fat products, and processed meats, increased lean meat and poultry intake, and increased amounts of physical activity, and modifications in eating habits and sedentary behavior further reduced body weight and cardiovascular risk 44 .…”
Section: Nutrition Lifestyle Treatments For Obese Patientmentioning
confidence: 99%